Pengaruh Media Pembelajaran Interaktif Berbantuan Genially Terhadap Minat Belajar Siswa Sekolah Dasar - Rezkillah, Inang Irma; Mariyati, Yuni; Muhdar, Syafruddin (Jurnal Ilmiah Profesi Pendidikan, 2026)
In today’s digital era, the use of interactive learning media has become increasingly important for improving the quality of teaching and learning processes in elementary schools. One widely adopted innovation is Genially; therefore, this study was conducted to investigate the effect of using Genially-based interactive learning media on students’ learning interest at MI NW Montong Selat. This research employed a quantitative approach with a quasi-experimental method, in which fourth-grade students served as the control group using picture-based learning media, while fifth-grade students served as the experimental group using Genially interactive learning media. Data collection techniques included learning interest questionnaires and observation of learning activities. The collected data were normally distributed, with significance values of 0.109 in the control class and 0.103 in the experimental class. Both classes were homogeneous, with a significance value of 0.806. The results of the independent t-test showed that the t-value (2.28) was less than the t-table (1.684), indicating a significant difference between the two classes. The findings concluded that the use of Genially-based interactive learning media had a positive and significant effect on students’ learning interest.